Evolution of Functional Family Therapy as an Evidence‐Based Practice for Adolescents with Disruptive Behavior Problems. Issue 3 (22nd June 2016) - Robbins, Michael S.; Alexander, James F.; Turner, Charles W.; Hollimon, Amy
Abstract : This article summarizes the evolution of functional family therapy (FFT) based upon four decades of clinical practice and scientific scrutiny through research evidence. FFT research has evolved from an initial focus upon clinical process research, which examined sequential exchanges between therapists and family members. A key element of this research has been an examination of the way in which clinicians acquire, consolidate, and maintain the skills needed to implement FFT effectively with youth and families. Many randomized efficacy and effectiveness studies have evaluated the impact of FFT across diverse clinical populations. Subsequent research investigated factors that influence the effectiveness of implementation across more than 300 clinical settings in which more than 2, 500 trained clinicians have provided service to nearly 400, 000 families. Another important set of investigations concerned the cost‐effectiveness of the interventions.